Counseling theories and counselor education - Parker, Clyde A. (Boston, Massachusetts : Houghton Mifflin Company, 1968)
Professional counseling is still a relatively new institution in our society, and some critics continue to doubt the uniform effectiveness of counseling, However, it does seem clear that a counselor is able to effect changes in a client's behaviors, attitudes, and emotions- -changes that should signal improvement in the client's condition but may sometimes indicate a deterioration. Recognition of the possibility of negative effects places a heavy burden on counselor educators who have the responsibility of certifying a counselor's competence.
1. Issues, evidence, and a beginning -- 2. The counselor as a role-free person -- 3. Fact and choice in counseling and counselor education: a cognitive viewpoint -- 4. The Psychological intervie2 as a discovery machine -- 5. Counselor education: facilitating the development of a helping person.
Includes index.
Keywords: COUNSELING